PALYNOLOGICAL ASSEMBLAGES OF CONTINENTAL LOWER TRIASSIC IN EASTERN EUROPE AND THEIR INTERREGIONAL CORRELATION. PAPER 1: PALYNOLOGICAL ASSEMBLAGES OF THE INDUAN STAGE - Yaroshenko O.P.; Lozovsky V.R. (My University, 2004)
Four palynological assemblages characteristic of the Nedubrovo, basal Astashikha, middle-upper Astashikha-Ryabi, and Sarafanikha members of the Vokhma Formation are distinguished in Lower Triassic continental deposits of the Moscow syneclise. Palynological assemblages of similar composition are known from continental deposits in other areas of the East European platform and from marine sediments bearing ammonites and conodonts. Palynological assemblages Cycadopites sp.-Klausipollenites schaubergeri and Striatoabieites richteri-K. schaubergeri are correlated with the Otoceras concavum Zone of the ammonite scale. The Densoisporites complicatus-Ephedripites sp. assemblage spans the range of the Otoceras boreale Zone, and the Ephedripites permasensis-Pechorosporites disertus assemblage is typical of the Ophiceras commune Zone and probably of a higher part of the Induan Stage. The established correlation is consistent with data obtained by ecotone and paleomagnetic methods.
Keywords: Mesozoic::Triassic::Lower::Induan; Мезозой::Триасовая::Нижний::Индский